Movimento na composição musical: uma abordagem à luz do pensamento de Paul Klee e Gilles Deleuze - Sergio Rodrigo Ribeiro Lacerda (2012)
The composer, in speaking of his own compositional process, confronts a series of challenges. Constantly there is the threat of the intellectual and technical approach not attains the wealth experienced at a creative process. This work seeks position itself face these challenges, relating musical creation and reflection from a multidisciplinary perspective that considers both the technical aspects as poetic aspects involved in artistic creation. Reflections of Deleuze and Klee on artistic creation establish a theoretical framework from which a set of six works of the author, written between 2010 and 2012, are discussed. The discussion will be focused on the concept capture of forces.